A Neural and Fuzzy Logic Based Control Scheme for a Shunt Active Power Filter - H. Laib; A. Chaghi; P. Wira (Recent Advances in Electrical Engineering and Control Applications, 2017)
In this paper, a three-phase shunt active filter is used to compensate for current harmonics and reactive power in three-phase distribution network system. In order to improve its performances, artificial neural networks and fuzzy logic approaches are used to control this device. The first controller, based on ADALINE networks, is used with the direct method in order to identify precisely the necessary currents to reduce the harmonics and to compensate reactive power. The neural network inputs are based on a decomposition of the measured currents. This decomposition is also based on the Fourier series analysis of the current signals and Least Mean Square (LMS) training algorithm to carry out the weights. In this case, three ADALINE are used to extract the fundamental component of the distorted line current directly from the three phase space. The second controller is the fuzzy logic controller, used to …